Adsorption and removal of phenoxy acetic herbicides from water by using commercial activated carbons: experimental and computational studies - Pila, Matías (2018)
In this study, commercial activated carbons (GAB and CBP) were successfully used for the removal of two phenoxy acetic class-herbicides, 4-chloro-2-methyl phenoxy acetic acid and 2.4-dichlorophenoxy acetic acid (MCPA and 2.4-D) from aqueous solution. The adsorbent materials were characterized, and their equilibrium adsorption capacity was evaluated. The results suggest that the microporous properties of GAB activated carbon enhanced the adsorption capacity, in comparison to CBP carbon. Thus, the increasing in the ionic strength favored the adsorption removal of both pesticides, indicating that electrostatic interactions between the pollutant and the adsorbate surface are governing the adsorption mechanism, but increasing pH values decreased adsorption capacity. Experimental data for equilibrium was analyzed by two models: Langmuir and Freundlich. Finally, computational simulation studies were used to explore both the geometry and energy of the pesticides adsorption.